2021
DOI: 10.1136/bmjopen-2020-042140
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and outcomes in patients hospitalised with COVID-19 infection in East London: an observational cohort study

Abstract: ObjectiveTo describe outcomes within different ethnic groups of a cohort of hospitalised patients with confirmed COVID-19 infection. To quantify and describe the impact of a number of prognostic factors, including frailty and inflammatory markers.SettingFive acute National Health Service Hospitals in east London.DesignProspectively defined observational study using registry data.Participants1737 patients aged 16 years or over admitted to hospital with confirmed COVID-19 infection between 1 January and 13 May 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 27 publications
4
102
1
Order By: Relevance
“…Our study showed a high prevalence of patients from Black, Asian and minority ethnic (BAME) backgrounds, reflecting the local general population. However, unlike the previously published studies on BAME patients [13,19], we were not able to demonstrate any significant differences in outcomes according to ethnicity in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study showed a high prevalence of patients from Black, Asian and minority ethnic (BAME) backgrounds, reflecting the local general population. However, unlike the previously published studies on BAME patients [13,19], we were not able to demonstrate any significant differences in outcomes according to ethnicity in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…This study was performed as a sub-population analysis within the ethnicity and outcomes in patients hospitalised with COVID-19 infection in East London (ethical) study [13], involving analysis of routinely collected patient data by members of the usual care team and approved by NHS England Health Research Authority (IRAS Project ID 283,512).…”
Section: Methodsmentioning
confidence: 99%
“…The study design in seven studies was prospective cohort studies [8,12,[17][18][19][20]22], while the others were all retrospective cohort studies [11,13,15,16,21,[23][24][25]. There were a variety of countries, ranging from the U.S. to European countries, with 2 in the USA [11,24], five in the UK [8,13,15,19,22], 1 in Turkey [18],1 in France [16], 1 in Switzerland [23], 2 in Spain [21,25], 2 in Sweden [12,20], and 1 in the UK and Italy [17]. Of these, 13 study settings were in the hospital [8, 11-13, 15-20, 22, 23, 25] and two were in a nursing home [21,24].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…The largest sample size was in Turkey [18], with 18,234 patients, and the smallest was in France [16], with 94 patients. Among all of the included studies, 11 studies used the clinical frailty scale (CFS) as an assessment tool for frailty [8,12,13,15,17,[19][20][21][22][23]25], one used the hospital frailty risk score [18], one used the frailty index [24], one used the palliative performance scale [11] and one used the frail nondisabled questionnaire [16]. Detailed information of adjustment variables for each study was shown in Supplemental Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation